Nano- and Microsensors for In Vivo Real-Time Electrochemical Analysis: Present and Future Perspectives - Vaneev, Alexander N.; Timoshenko, Roman V.; Gorelkin, Petr V.; Klyachko, Natalia L.; Korchev, Yuri E.; Erofeev, Alexander S. (Nanomaterials (Basel, Switzerland), 2022)
Electrochemical nano- and microsensors have been a useful tool for measuring different analytes because of their small size, sensitivity, and favorable electrochemical properties. Using such sensors, it is possible to study physiological mechanisms at the cellular, tissue, and organ levels and determine the state of health and diseases. In this review, we highlight recent advances in the application of electrochemical sensors for measuring neurotransmitters, oxygen, ascorbate, drugs, pH values, and other analytes in vivo. The evolution of electrochemical sensors is discussed, with a particular focus on the development of significant fabrication schemes. Finally, we highlight the extensive applications of electrochemical sensors in medicine and biological science.